Development of the European Market for Environmental Goods and Services and its Financial Support - Skorokhod, Iryna; Skorokhod, Daryna (Journal of Finance and Financial Law, 2022)
The purpose of the article is to analyze and assess the situation of the market for environmental goods and services in the EU as well as the formation of its support and regulation system. Methodology: The market for environmental goods and services has experienced the dynamic growth and development in the last two decades, especially in economically developed countries. The research concerns the peculiarities of the development of the organic products market, sources of support for the development of organic production in the EU. The research uses the desk research method, which provides a possibility of using a wide range of materials in various areas and periods. Additionally, relevant legal acts, official documents and reports were used in the study. Results of the research: The structure of certified agricultural lands in the EU is thoroughly analyzed in the article. Emphasis is placed on the study of the EU market for organic products development peculiarities, which include a constant growth of demand for these products and their rising prices. The main elements of the ecological goods and services market regulation system are also characterized. The conclusions contained in the article refer to the possibility of using one of these instruments: financing from the European Agricultural Guarantee Fund and the European Agricultural Fund for Rural Development, crediting, venture financing, green bonds, fundraising, crowd funding, crowd landing as well as own means of enterprises. Generally, financial support should be more flexible and tailored to the needs of beneficiaries.